The Effects of Legume-Cereal Intercropping on the Symbiotically Fixed N2 in Soybean, N Accumulation, and C Allocation - Monika Toleikiene; Raminta Skipityte; Ruta Bariseviciute; Juliana Trindade Martins; Jim Rasmussen (Plants)
Intercropping soybean and wheat can enhance soil fertility through increased nitrogen fixation, optimize resource use, and boost overall crop productivity, thereby promoting sustainable agricultural practices. Thus, this research examines nitrogen accumulation and carbon allocation in the intercrops of soybean and spring wheat, as well as the nitrogen fixation in soybean using the 15N isotope dilution method and 13C-CO2 pulse labeling. Soybean and spring wheat were grown as monocultures and mixtures in different densities, containing 4 or 8 plants of wheat, either 1 or 3 soybean plants, or a mixture of both. The intercropping had a significant impact on soybean atmospheric nitrogen fixation. When grown in mixtures with wheat, soybean accumulated more than twice as much atmospheric nitrogen in the roots; however, the effect on total accumulated N per plant was rather negative and plant densities dependent. Growing mixtures at low densities of soybean and high densities of wheat had a better effect on the total nitrogen content of plants. Overall, intercropping caused a significant redistribution of carbon and nitrogen in plants. Carbon allocation was influenced in soybeans but not in wheat grown in monocultures and in mixtures. Intercropping also positively influenced carbon accumulation, with the increase in carbon density being more pronounced in the roots than in the shoots for both species.